Human Capital and Growth : The Recovered Role of Education Systems - Dessus, Sebastien (World Bank, Washington, DC, 2014)
Recent empirical studies question conventional wisdom about the importance of education to growth. These results partly reflect how international differences in the quality of education systems--defined by the systems' ability to produce one marginal unit of productive human capital--are not taken into account. The author estimates neoclassical growth models on panel data in which the elasticity of human capital depends stochastically on different characteristics of the education system. Among characteristics that explain differences in quality are education infrastructure, the initial endowment of human capital, and the ability to distribute educational services equally among potential students. Giving priority to primary education for all rather than secondary education to a few is more likely to foster growth (for the same fiscal burden). But parallel actions are also probably needed--for example, promoting institutions that motivate skilled workers to spend time on growth-promoting activities and encouraging the inflow of foreign technologies to maximize the social return to public investment in education.